Parameter-elliptic problems and interpolation with a function parameter - Murach, A. A.; Anop, A. V. (Methods of Functional Analysis and Topology, 2014)
Parameter-elliptic boundary-value problems are investigated on the extended Sobolev scale. This scale consists of all Hilbert spaces that are interpolation spaces with respect to a Hilbert Sobolev scale. The latter are the Hörmander spaces B_2,k for which the smoothness index k is an arbitrary radial function RO-varying at +∞. We prove that the operator corresponding to this problem sets isomorphisms between appropriate Hörmander spaces provided the absolute value of the parameter is large enough. For solutions to the problem, we establish two-sided estimates, in which the constants are independent of the parameter.